(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
The present study proposes other perspectives to think about different childhoods, understanding children as active social actors in their identity and social processes. As a result, they are seen as a threat to adult culture, especially when they deviate from the binary norm. Children in dissidence, however, find gaps in their daily lives and in theater classes to build knowledge and cultures as a form of resistance. Thus, it is believed in the importance of discussing ways to promote social and epistemic justice in relation to childhoods and children in dissidence from the field of Performing Arts and Theater Pedagogies.